Comparative Analysis of Animal Structure Practicum Results Based on Online and Offline Knocking Systems - Maspupah , Meti; Hidayah, Nurul (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Animal structure lectures are a learning process that is integrated with practicum activities which are mandatory activities and must be carried out in one semester in tandem with the implementation of theoretical learning. This study aims to find out the comparison of student midterm exam scores using the online and offline ketok system. The method used is a comparative analysis of midterm exam scores in two different classes. The instrument used was data on student midterm exam scores in two animal structure practicum classes. The results showed that the average midterm exam score in the class with the online knock system was 52.9 with the highest score 80 and the lowest 30, while in the offline knock system class it was 47.3 with the highest score 80 and the lowest 25 out of a total sample of 22 students in each class. Based on the research results, it can be concluded that the different midterm exam methods in the animal structure practicum have a significant influence on the practicum exam results